Dewetting-induced collapse of hydrophobic particles - Huang, X. (National Academy of Sciences, 2003)
A molecular dynamics study of the depletion of water (drying) around a single and between two hydrophobic nanoscale oblate plates in explicit water as a function of the distance of separation between them, their size, and the strength of the attraction between the plates and the water molecules is presented. A simple macroscopic thermodynamic model based on Young's law successfully predicts drying between the stacked plates and accounts for the free-energy barriers to this drying. However, because drying around a single plate is not macroscopic, a molecular theory is required to describe it. The data are consistent with the rate-determining step in the hydrophobic collapse of the two plates being a large-scale drying fluctuation, characterized by a free-energy barrier that grows with particle size.